Business Model Implementation within Networked Enterprises: A Case Study on a Finnish Pharmaceutical Project - Sam Solaimani; Marikka Heikkilä; Harry Bouwman (John Wiley & Sons, Inc, 2022)
In many entrepreneurial projects, the concept of the business model (BM) is used to describe a business idea at a high-level and in a holistic way. However, existing literature pays less attention to implementation (or execution) of BM. Implementation becomes more complex when a BM is proposed by or requires a network of collaborating enterprises. The aim of this paper is to provide an approach based on empirical research that supports BM transition from design to implementation. The empirical data used in this paper is based on a case study involving an innovative project in the pharmaceutical sector in Finland. The case analysis demonstrates how a high-level BM needs careful consideration of its operational components from a network perspective to secure both value creation and capture. Drawing on the analysis, six concluding propositions on BM implementation in networked settings are put forward.